System-level power-to-gas energy storage for high penetrations of variable renewables. (25th January 2018) - Lyseng, B.; Niet, T.; English, J.; Keller, V.; Palmer-Wilson, K.; Robertson, B.; Rowe, A.; Wild, P.
Abstract: According to outlooks by the IEA and the U.S. EIA, renewables will become the largest source of electricity by 2050 if global temperature rise is to be limited to 2 °C. However, at penetrations greater than 30%, curtailment of wind and solar can be significant in even the most flexible systems. Energy storage can reduce curtailment and increase utilisation of variable renewables. Power-to-gas is a form of long-term storage based on electrolytic production of hydrogen. This research models the co-sizing of wind and solar PV capacity and electrolyser capacity in a jurisdiction targeting 80% penetration of variable renewable electricity. Results indicate that power-to-gas can reduce required wind and solar capacity by as much as 23% and curtailment by as much as 87%. While the majority of charging events last less than 12 h, the majority of the total annual stored energy comes from longer-term events. Additional scenarios reveal that geographic diversity of wind farms reduces capacity requirements, but the same benefit is not found for distributing solar PV. Highlights: 80% variable renewable electricity (VRE) penetration is targeted. Power-to-gas (PtG) provides system-level storage. Electrolyser and VRE capacity are co-sized to meet the VRE target. PtG reduces VRE capacity by as much as 23% and curtailment by up to 87%. Charging events longer than 12 h account for most of the stored energy.